PERBANDINGAN TINGKAT KOHESIVITAS ANTARA SISWA RINTISAN SEKOLAH BERSTANDAR INTERNASIONAL (RSBI) DAN SEKOLAH STANDAR NASIONAL (SSN) (STUDI PADA KELAS XI SMAN 15 SURABAYA DAN SISWA KELAS XI SMAN 11 SURABAYA) - IQBAL AGUNG SY, M (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The quality of education is determined by the curriculum. Curriculum as the education program consist of some other important aspects, such as the subject, teaching activity, education program for students, and also the results of that learning activity. In Physical education health sports have an important role and value in the formation of student’s caracters. One of the important value is the cohesiveness of student in a group. The research problem of this study are: 1) how is the cohesiveness level of RSBI Student and SSN Student; 2) is there any comparison between cohesiveness level of RSBI Student and SSN Student in SMAN 15 and SMAN 11 Surabaya. The sample of this research is using cluster sampling which is choosing the area of the population, not the individual so it called as group of area or cluster. The subject was 30 students of XI IPA 8 SMAN 15 Surabaya and 30 students of XI IPA 4 SMAN 11 Surabaya. The method in this analysis using statistical methods, quantitative descriptive, and Independent sample T-Test. And the data was taken using questionnaire of cohesiveness. The research concluded that: 1) the amount of mean value of cohesiveness level of XI IPA 8 SMAN 15 Surabaya is 98,47 which is belong to medium category of the total amount of 30 the students. And the mean value of cohesiveness level of XI IPA 4 SMAN 11 Surabaya is 93,73 which is also belong to medium category of the total amount of 30 students. The result value cohesiveness scale of the standard deviation of XI IPA 8 SMAN 15 Surabaya is 11,135, and the variance value of 123,982. With the lowest score at 63 and the highest grade of 115. And for students of XI IPA 4 SMAN 11 Surabaya has mean value of 93,73, the value of the standard deviation of 13,096, and the variance value of 171,513 with the lowest score at 63 and the highest score of 115. 2) The results of the independent sample t-test obtained: Tcount (-1,498) > Ttable (2,0105). In other words that there is no significant comparison of RSBI Student (XI IPA 8 SMAN 15 Surabaya) and SSN Student (XI IPA 4 SMAN 11 Surabaya). Keywords: Cohesiveness Level, RSBI, SSN